Intervention of Specific Nutrition and Sensitive Nutrition with Nutritional Status of Under Two-Year Infants in Family Planning Village as Efforts to Face the Demographic Bonus (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
KB Village, through the family development program for children under five years (ttoddler) participated involved interventions of sensitive nutrition and specific nutrition. The purpose of this study is to see the role of the KB village in preventing stunting in toddlers (children under five years) and to find the dominant factors that influence it. The research design is cross sectional with 85 samples of under two-year infants (baduta), the mothers, 5 of KB Villages in Palangka Raya and 2 of KB Villages in East Barito Regency (Bartim). The study is conducted from June to October 2018. Statistical analysis using chi square (Î± = 5%) with the results of the test Ï 0.02 Î± 0.05 that there is a relationship of intervention programs of sensitive nutrition and specific nutrition with the nutritional status of children under five years (toddler). The dominant factor in the nutritional status of under two-year infants (baduta) is exclusive breastfeeding with a value of Ï 0.012 0.05, RR = 6.702 (95% CI 1.518-29.579), motherâ€™s education Ï 0.001 0.05, RR 5.281 (95% CI 1.970-14.158). There is a need for family development programs for children under five years and adolescence in implementing intervention programs of sensitive nutrition and specific nutrition, collaborating with the community, managing records and reporting based on success indicators, partnering with policy holders and community empowerment.